PENOLAKAN MASYARAKAT TERHADAP REKLAMASI TELUK BENOA PROVINSI BALI - Dewi, Gangga Santi (Diponegoro Private Law Review, 2019)
ABSTRACT  The need for land for tourism in Bali makes the government want to reclaim Benoa Bay. Rejection of Benoa Bay reclamation is a social phenomenon that occurs in Balinese society. Based on the results of the study, the reason Bali people reject reclamation because it has an impact on social aspects, cultural customs and the environment and solutions to conflicts that occur due to the refusal of Benoa Bay reclamation requires clear policies related to land regulation resulting from reclamation that have no negative impact on cultural and environmental customs in Bali